Disinformation in the Spanish public debate: an analysis of political speeches in the Congress of Deputies - Domínguez-García, Ricardo; Velasco-Molpeceres, Ana; Pérez-Curiel, Concha (Frontiers in Communication, 2024)
Disinformation is one of the main challenges faced by modern democratic societies, becoming a crucial focus of study in political communication. Terms such as lie, falsehood, hoax, disinformation, or post-truth have become part of the daily language of the media, featured in numerous scientific studies, and entered political discourse. With the aim of delving into and determining the characteristic features of Spanish politicians' discourse on disinformation, a methodology of quantitative and qualitative content analysis is applied to a total of 1,115 interventions by members of the Congress of Deputies during the first year of the COVID-19 pandemic in Spain. This period is chosen due to its high levels of disinformation and polarization. The results indicate that the issue of disinformation is a minor topic on the Spanish political agenda. Furthermore, metrics confirm a much higher use of terms such as lie, false, and hoax, to the detriment of other words like disinformation or post-truth. An impact of the pandemic on the main themes related to this phenomenon is also detected, with health and the economy being the primary frames identified. From an interpretative perspective, this is attributed to the tendency of Spanish politicians to use this issue as just one element within a polarizing and confrontational rhetoric, generally eschewing proactive debates on the measures needed to address disinformation.